2009
DOI: 10.1007/s11242-009-9358-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Kinetic Interphase Mass Transfer for Two-Phase Flow in Porous Media Including Fluid–Fluid Interfacial Area

Abstract: Interphase mass transfer in porous media takes place across fluid-fluid interfaces. At the field scale, this is almost always a kinetic process and its rate is highly dependent on the amount of fluid-fluid interfacial area. Having no means to determine the interfacial area, modelers usually either neglect kinetics of mass transfer and assume local equilibrium between phases or they estimate interfacial area using lumped parameter approaches (in DNAPL pool dissolution) or a dual domain approach (for air spargin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…This allows for the conclusion that the inclusion of fluid-fluid interfacial area into the capillary pressure-saturation relationship makes hysteresis disappear or, at least, reduces it down to a very small value. Niessner & Hassanizadeh (2008;2009a;b) have modeled two-phase flow-using the thermodynamically-based set of equations developed by Hassanizadeh & Gray (1990)-and showed that this interfacial-area-based model is indeed able to model hysteresis as well as kinetic interphase mass and also energy transfer in a physically-based way.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows for the conclusion that the inclusion of fluid-fluid interfacial area into the capillary pressure-saturation relationship makes hysteresis disappear or, at least, reduces it down to a very small value. Niessner & Hassanizadeh (2008;2009a;b) have modeled two-phase flow-using the thermodynamically-based set of equations developed by Hassanizadeh & Gray (1990)-and showed that this interfacial-area-based model is indeed able to model hysteresis as well as kinetic interphase mass and also energy transfer in a physically-based way.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In order to do numerical modeling, simplifying assumptions need to be made. In the following, we present such a simplified equation system as was derived in Niessner & Hassanizadeh (2009a). This set of balance equations can be described by six mass and three momentum balance equations.…”
Section: Simplified Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaporation of water from the formation brine into the injected CO 2 is a complex phenomenon: It occurs due to the mutual solubility of CO 2 and water Pruess 2005, 2010). The rate of evaporation depends on factors including interfacial area between brine and CO 2 (Niessner and Hassanizadeh 2009), persistence of liquid pathways to supply brine to the drying front (Lehmann et al 2008;Nachshon et al 2011;Shokri et al 2010), CO 2 flow velocity (Zuluaga et al 2001) and thermodynamic properties which determine the vapor pressure. The efficiency of evaporation determines the steepness of the gradient in brine saturation inside the porous medium and therefore the significance of capillary-driven flow.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one would expect physical approaches to modeling kinetic interphase mass and heat transfer to contain the interfacial area between the phases as a variable. Recently, a two-phase flow and solute transport model was developed that included interfacial area as a state variable [36]. In that model, interphase mass transfer was modeled as a kinetic process.…”
mentioning
confidence: 99%